Silk fabric and preparation method thereof

By degumming the cocoon and combining it with functionalized polysiloxanes, modified phase-change microcapsules and other materials, silk fibers with multiple modification properties are prepared, which solves the problems of yellowing, moldy and flammable existing silk fabrics, and realizes the development of high-performance silk fabrics.

CN119061523BActive Publication Date: 2025-03-21HUZHOU XINYU SILK WEAVING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411546590.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-21
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing silk fabrics have disadvantages such as yellowing, moldy and flammable, which limit their further development.

Method used

Silk fibroin solution is prepared by degumming the silk cocoon and combining it with functionalized polysiloxanes, modified phase change microcapsules and other materials, and silk fibers are made by coaxial electrospinning, and finally textile it into a silk fabric with flame retardant, antibacterial, UV-proof, warm and hydrophobic properties.

Benefits of technology

It improves the breaking strength, flame retardant properties, antibacterial properties, UV resistance, warmth and hydrophobic properties of silk fabrics, and broadens its industrial application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses a silk fabric and a preparation method thereof, and relates to the field of silk fabrics. When preparing the silk fabric, the present invention prepares a silk fibroin solution by degumming and dissolving the silk cocoon; reacts octamethylcyclotetrasiloxane, flame retardant modified siloxane, antibacterial modified siloxane and tetramethyldisiloxane to prepare functionalized polysiloxane; reacts light-absorbing monomers, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde and urea to prepare modified phase-change microcapsules; coaxial electrostatic spinning of the silk fibroin solution, functionalized polysiloxane and modified phase-change microcapsules to prepare silk fibers; and weaving the silk fibroin into a fabric and treating it with a trifluoropropylene chloroplatinic acid mixed solution to prepare the fabric. The silk fabric prepared by the present invention has good breaking strength, flame retardant properties, antibacterial properties, UV protection properties, warmth retention properties and hydrophobic properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of silk fabrics, in particular to a silk fabric and a preparation method thereof. Background Art

[0002] Bombyx mori silk is one of the earliest known and largest natural polymer materials. Bombyx mori silk has an elegant pearl-like luster, good air permeability, strong hygroscopicity, good hand feel, and has excellent strength and ductility, excellent biocompatibility, biodegradability and environmental stability. It is known as the "Queen of Fibers" and is also a green and environmentally friendly fiber that adapts to the development of modern society. Textiles processed from silk fibers have always occupied an important position in commercial trade.

[0003] With the development of society, economy and culture and the improvement of living standards, people's awareness of environmental protection, health and safety is constantly improving. How to effectively modify silk so that it can play its strengths and avoid its weaknesses, improve the added value of silk and silk products, and expand its industrial field has become the focus of research by domestic and foreign scholars in recent years and even in the future. Silk has the disadvantages of being easy to turn yellow, easy to mold, and easy to flammable, which limits the further development of silk fabrics. The silk fabric prepared by the present invention has good breaking strength, flame retardant properties, antibacterial properties, UV protection, thermal insulation and hydrophobic properties, and has broad market prospects. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing silk fabric to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A silk fabric, the silk fabric is prepared by degumming and dissolving silk cocoons to obtain a fibroin solution; reacting octamethylcyclotetrasiloxane, flame-retardant modified siloxane, antibacterial modified siloxane and tetramethyldisiloxane to obtain functionalized polysiloxane; reacting light-absorbing monomers, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde and urea to obtain modified phase-change microcapsules; coaxially electrostatically spinning the fibroin solution, functionalized polysiloxane and modified phase-change microcapsules to obtain silk fibers; and weaving the silk fibers into fabrics and treating them with a trifluoropropylene chloroplatinic acid mixed solution to obtain the fabrics.

[0007] A method for preparing a silk fabric comprises the following steps:

[0008] (1) The silk cocoon is peeled into a single layer and placed in a sodium carbonate aqueous solution with a mass fraction of 0.5% to 0.7%, boiled for 25 to 30 minutes, cooled to room temperature, washed with deionized water for 3 to 5 times, and naturally air-dried to obtain degummed silk; the degummed silk and a 9 to 10 mol / L lithium bromide aqueous solution are mixed at a mass ratio of 1: (8 to 10), stirred at 600 to 800 r / min at 35 to 45°C for 25 to 30 minutes, centrifuged to obtain the supernatant, and diluted with deionized water 1.5 to 1.7 times the supernatant, placed in a cellulose dialysis bag, and dialyzed with deionized water for 70 to 80 hours, and concentrated under vacuum at 20 to 30°C to a solute mass fraction of 35% to 40% to obtain a silk fibroin solution;

[0009] (2) Octamethylcyclotetrasiloxane, flame retardant modified siloxane, antibacterial modified siloxane and tetramethylammonium hydroxide siliconate are mixed in a mass ratio of 1: (0.5-0.7): (0.5-0.7): (0.01-0.03), nitrogen is passed for 10-20 min, and the mixture is stirred at 100-200 r / min at 80-90 °C for 2-3 h. Tetramethyldisiloxane (0.2-0.4 times the mass of octamethylcyclotetrasiloxane) is added, the temperature is raised to 95-105 °C and stirring is continued for 7-9 h. The temperature is raised to 130-140 °C at 10-20 °C / min and stirring is continued for 40-50 min. The mixture is distilled at 0.1-0.3 MPa for 1-2 h to obtain functionalized polysiloxane.

[0010] (3) 2-chloro-4,6-diamino-1,3,5-triazine, anhydrous aluminum chloride and chlorobenzene are mixed uniformly in a mass ratio of 1:(0.3-0.4):(10-12), stirred at 200-300 r / min for 20-30 min at 0-3°C, then 0.6-0.8 times the mass of resorcinol of 2-chloro-4,6-diamino-1,3,5-triazine is added, the temperature is raised to 75-85°C, stirred for 4-6 h, cooled naturally to room temperature, extracted and washed with chloroform for 3-5 times, and dried at 60-70°C for 10-12 h to obtain a light-absorbing monomer;

[0011] (4) Mix the light-absorbing monomer, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde, urea and deionized water in a mass ratio of 1: (1.4-1.6): (10-14): (4-6): (70-90), adjust the pH to 8.3-8.7 with triethanolamine, and stir at 350-450 r / min for 50-70 min at 65-75 °C to obtain a prepolymer solution; mix n-hexadecane, sodium dodecyl sulfate, Tween-80 and deionized water in a mass ratio of 1: (0.03-0.05): (0.008-0.012): ( 4~6) Mix well, stir at 1800~2000r / min for 5~15min at room temperature to obtain an emulsion; cool the prepolymer solution to 45~55℃, adjust the speed to 1800~2000r / min, add 1.8~2.2 times the mass of the prepolymer solution, adjust the pH to 2.5 with 10% ammonium chloride solution and 10% citric acid within 2.5h, stir and react for 3~5h, cool to room temperature, filter, wash the filter residue with deionized water and anhydrous ethanol for 3~5 times respectively, and dry at 65~75℃ for 3~5h to obtain modified phase change microcapsules;

[0012] (5) The silk fibroin solution and the functionalized polysiloxane were mixed at a mass ratio of 1:(0.5-0.7), concentrated at 20-30°C and 10-20Pa to a solute mass fraction of 50%-60%, and polyethylene glycol (0.01-0.02 times the mass of the silk fibroin solution) was added, and ultrasonic dispersion was performed at 30-40°C and 25-35kHz for 15-20min to prepare a shell fluid; the modified phase change microcapsules and anhydrous ethanol were mixed at a mass ratio of 1:(20-30), and ultrasonic dispersion was performed at 30-40°C and 25-35kHz for 15-20min to prepare a core fluid; the shell fluid and the core fluid were separated by a stirring process. Coaxial nozzle extrusion spinning, the inner diameter of the outer ring of the nozzle is 0.7mm, the inner diameter of the inner ring of the nozzle is 0.3mm, the extrusion speed is 2.8~3.2μL / min, the receiving distance is 10~12cm, the spinning temperature is 23~27℃, the relative humidity is 40%~50%, soaked in 0.6~0.8mol / L calcium chloride aqueous solution at 20~30℃ for 15~20s, taken out and immersed in 1.3~1.5g / L sodium carbonate aqueous solution, let stand at 55~65℃ for 60~80min, taken out, washed with deionized water and anhydrous ethanol 3~5 times, and vacuum dried at 30~40℃ for 6~8h to obtain silk fiber.

[0013] (6) The silk fibers were warped on a warping machine and then woven into plain fabrics using a fully automatic rapier loom with a warp density of 600 strands / 10 cm and a weft density of 500 strands / 10 cm. The fabrics were then treated with a mixed solution of trifluoropropylene chloroplatinic acid as a post-finishing solution. The fabrics were subjected to two immersion and two rolling treatments with a rolling residue rate of 80%. The fabrics were allowed to stand at 70-80°C for 10-20 min, heated to 110-130°C, allowed to stand for 20-40 min, washed with deionized water for 8-12 min, and air-dried to obtain silk fabrics.

[0014] As an optimization, the silk cocoon in step (1) is a double-palace cocoon produced in Suzhou, Jiangsu.

[0015] As an optimization, the flame retardant modified siloxane described in step (2) is prepared by stirring vinylmethyldimethoxysilane, p-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and anhydrous ethanol in a mass ratio of 1: (0.7-0.9): (0.04-0.06): (13-17) at 20-30°C and 400-600 r / min for 8-10 hours.

[0016] As an optimization, the antibacterial modified siloxane described in step (2) is prepared by stirring 3-chloropropyldimethoxymethylsilane, 3-dimethylaminochloropropane hydrochloride, and anhydrous ethanol in a mass ratio of 1: (0.7-0.9): (13-17) at 70-90°C and 400-600 r / min for 10-14 hours.

[0017] As an optimization, the reaction process of the functionalized polysiloxane in step (2) is as follows: .

[0018] As an optimization, the trifluoropropylene and chloroplatinic acid mixed solution described in step (6) is prepared by mixing trifluoropropylene, chloroplatinic acid, and dichloromethane in a mass ratio of 1:0.1:3.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] When preparing silk fabrics, the present invention comprises the following steps: degumming and dissolving silk cocoons to obtain a silk protein solution; reacting vinylmethyldimethoxysilane with p-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to obtain a flame retardant modified siloxane; reacting 3-chloropropyldimethoxymethylsilane with 3-dimethylaminochloropropane hydrochloride to obtain an antibacterial modified siloxane; reacting octamethylcyclotetrasiloxane, flame retardant modified siloxane, antibacterial modified siloxane with tetramethyldisiloxane to obtain a functional modified siloxane. The invention relates to a method for preparing a light-absorbing monomer by reacting 2-chloro-4,6-diamino-1,3,5-triazine with resorcinol; the light-absorbing monomer, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde and urea are reacted to obtain modified phase-change microcapsules; the silk fibroin solution, the functionalized polysiloxane and the modified phase-change microcapsules are subjected to coaxial electrospinning to obtain silk fibers; the silk fibers are spun into fabrics and treated with a mixed solution of trifluoropropylene chloroplatinic acid to obtain silk fabrics.

[0021] Firstly, octamethylcyclotetrasiloxane, flame retardant modified siloxane, antibacterial modified siloxane and tetramethyldisiloxane are reacted to obtain functionalized polysiloxane. The antibacterial modified siloxane is obtained by reacting 3-chloropropyldimethoxymethylsilane with 3-dimethylaminochloropropane hydrochloride. On the one hand, a quaternary ammonium salt structure is introduced. As a cationic antibacterial agent, the quaternary ammonium salt can have a good contact antibacterial effect and improve the antibacterial properties of silk fabrics. In addition, as a cation, it has a positive charge and can form electrostatic adsorption with the negatively charged silk fibroin in the silk fibroin solution, thereby further improving the combination of the functionalized polysiloxane and the silk fibroin and improving the breaking strength of the silk fabric. On the other hand, the end is a reactive The chlorine atoms in the functionalized polysiloxane can react with the abundant amino groups on the silk fibroin in the silk fibroin solution to form stable chemical crosslinks, thereby improving the breaking strength of the silk fabric; vinylmethyldimethoxysilane reacts with p-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to obtain flame-retardant modified siloxane, and the flame-retardant monomer DPOP is introduced into the functionalized polysiloxane through the reaction of double bonds with phosphorus and hydrogen, which can react with the silicon on the polysiloxane to form a silicon-phosphorus synergistic flame retardant, thereby effectively improving the flame retardant properties of the silk fabric; tetramethyldisiloxane makes the two ends of the functionalized polysiloxane have a silicon-hydrogen structure, which can react with the double bonds on the trifluoropropylene in the finishing solution to give the silk fabric good hydrophobic properties.

[0022] Secondly, 2-chloro-4,6-diamino-1,3,5-triazine reacts with resorcinol to obtain a light-absorbing monomer, which reacts with 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde and urea to obtain a modified phase-change microcapsule. 2-chloro-4,6-diamino-1,3,5-triazine can form a conjugated hydrogen bond six-membered ring with resorcinol, absorb ultraviolet light through the stretching vibration of hydrogen bonds, and convert the absorbed light energy into heat energy, which is stored in the phase-change microcapsule and slowly released, so that the silk fabric has good The anti-ultraviolet property makes the silk fabric have good thermal insulation performance; 2-vinyl-4,6-diamino-1,3,5-triazine introduces abundant double bonds on the surface of the modified phase change microcapsules, which can react with the silicon-hydrogen structure at both ends of the functionalized polysiloxane under the catalysis of chloroplatinic acid to form a stable chemical connection, thereby improving the breaking strength of the silk fabric; and the triazine structure has abundant nitrogen elements, which can form nitrogen-phosphorus-silicon synergistic flame retardant with the silicon-phosphorus on the functionalized polysiloxane, thereby further improving the flame retardant properties of the silk fabric. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] Embodiment 1:

[0025] A method for preparing a silk fabric comprises the following steps:

[0026] (1) The silk cocoon was peeled into a single layer and placed in a 0.5% by mass sodium carbonate aqueous solution, boiled for 25 min, cooled to room temperature, washed with deionized water for 3 times, and naturally air-dried to obtain degummed silk; the degummed silk and 9 mol / L lithium bromide aqueous solution were mixed at a mass ratio of 1:8, stirred at 600 r / min at 35°C for 25 min, centrifuged to obtain the supernatant, and diluted with 1.5 times the amount of deionized water, placed in a cellulose dialysis bag, and dialyzed with deionized water for 70 h, and concentrated under vacuum at 20°C to a solute mass fraction of 35% to obtain a silk fibroin solution;

[0027] (2) Vinylmethyldimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and anhydrous ethanol were stirred at a mass ratio of 1:0.7:0.04:13 at 20°C and 400 r / min for 8 hours to obtain flame retardant modified siloxane; 3-chloropropyldimethoxymethylsilane, 3-dimethylaminochloropropane hydrochloride, and anhydrous ethanol were stirred at a mass ratio of 1:0.7:13 at 70°C and 400 r / min for 10 hours to obtain antibacterial modified siloxane;

[0028] (3) Octamethylcyclotetrasiloxane, flame retardant modified siloxane, antibacterial modified siloxane and tetramethylammonium hydroxide siliconate were mixed in a mass ratio of 1:0.5:0.5:0.01, nitrogen was passed for 10 min, and the mixture was stirred at 80°C and 100 r / min for 2 h. Tetramethyldisiloxane (0.2 times the mass of octamethylcyclotetrasiloxane) was added, the temperature was raised to 95°C and stirring was continued for 7 h. The temperature was raised to 130°C at 10°C / min and stirring was continued for 40 min. The mixture was distilled at 0.1 MPa for 1 h to obtain functionalized polysiloxane.

[0029] (4) 2-chloro-4,6-diamino-1,3,5-triazine, anhydrous aluminum chloride and chlorobenzene were mixed uniformly in a mass ratio of 1:0.3:10, stirred at 200 r / min for 20 min at 0°C, and then 0.6 times the mass of resorcinol of 2-chloro-4,6-diamino-1,3,5-triazine was added, the temperature was raised to 75°C, stirred for 4 h, cooled naturally to room temperature, extracted and washed with chloroform three times, and dried at 60°C for 10 h to obtain a light-absorbing monomer;

[0030] (5) The light-absorbing monomer, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde, urea and deionized water were mixed in a mass ratio of 1:1.4:10:4:70, the pH value was adjusted to 8.3 with triethanolamine, and the mixture was stirred at 350 r / min for 50 min at 65°C to prepare a prepolymer solution; n-hexadecane, sodium dodecyl sulfate, Tween-80 and deionized water were mixed in a mass ratio of 1:0.03:0.008:4 and the mixture was heated at room temperature for 1 The mixture was stirred at 800 r / min for 5 min to obtain an emulsion; the prepolymer solution was cooled to 45°C, the rotation speed was adjusted to 1800 r / min, an emulsion 1.8 times the mass of the prepolymer solution was added, the pH was adjusted to 2.5 with 10% ammonium chloride solution and 10% citric acid within 2.5 h, the mixture was stirred for reaction for 3 h, the mixture was cooled to room temperature, filtered, the residue was washed with deionized water and anhydrous ethanol for 3 times respectively, and dried at 65°C for 3 h to obtain modified phase change microcapsules;

[0031] (6) The silk fibroin solution and functionalized polysiloxane were mixed at a mass ratio of 1:0.5, concentrated at 20°C and 10Pa to a solute mass fraction of 50%, and polyethylene glycol (0.01 times the mass of the silk fibroin solution) was added, and ultrasonic dispersion was carried out at 30°C and 25kHz for 15 minutes to prepare a shell fluid; the modified phase change microcapsules and anhydrous ethanol were mixed at a mass ratio of 1:20, and ultrasonic dispersion was carried out at 30°C and 25kHz for 15 minutes to prepare a core fluid; the shell fluid and the core fluid were passed through a coaxial Nozzle extrusion spinning, the inner diameter of the nozzle outer ring is 0.7mm, the inner diameter of the nozzle inner ring is 0.3mm, the extrusion speed is 2.8μL / min, the receiving distance is 10cm, the spinning temperature is 23℃, the relative humidity is 40%, soaked in a 0.6mol / L calcium chloride aqueous solution at 20℃ for 15s, taken out and immersed in a 1.3g / L sodium carbonate aqueous solution, left to stand at 55℃ for 60min, taken out, washed with deionized water and anhydrous ethanol 3 times, and vacuum dried at 30℃ for 6h to obtain silk fibers;

[0032] (7) The silk fibers were warped on a warping machine and then woven into plain fabrics using a fully automatic rapier loom with a warp density of 600 strands / 10 cm and a weft density of 500 strands / 10 cm. The fabrics were then finished using a trifluoropropylene chloroplatinic acid mixed solution. The fabrics were double dipped and double rolled with a rolling rate of 80%. The fabrics were allowed to stand at 70°C for 10 min, heated to 110-130°C and allowed to stand for 20 min. The fabrics were then washed with deionized water for 8 min and air-dried to obtain silk fabrics.

[0033] Embodiment 2:

[0034] A method for preparing a silk fabric comprises the following steps:

[0035] (1) The silkworm cocoons were peeled into a single layer and placed in a 0.6% by mass sodium carbonate aqueous solution, boiled for 27.5 min, cooled to room temperature, washed with deionized water for 4 times, and naturally air-dried to obtain degummed silk; the degummed silk and 9.5 mol / L lithium bromide aqueous solution were mixed in a mass ratio of 1:9, stirred at 700 r / min at 40°C for 27.5 min, centrifuged to obtain the supernatant, diluted with 1.6 times the amount of deionized water, placed in a cellulose dialysis bag, and dialyzed with deionized water for 75 h, and concentrated under vacuum at 25°C to a solute mass fraction of 37.5% to obtain a silk fibroin solution;

[0036] (2) Vinylmethyldimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and anhydrous ethanol were stirred at 25°C and 500 r / min for 9 hours at a mass ratio of 1:0.8:0.05:15 to obtain flame-retardant modified siloxane; 3-chloropropyldimethoxymethylsilane, 3-dimethylaminochloropropane hydrochloride, and anhydrous ethanol were stirred at 80°C and 500 r / min for 12 hours at a mass ratio of 1:0.8:15 to obtain antibacterial modified siloxane;

[0037] (3) Octamethylcyclotetrasiloxane, flame retardant modified siloxane, antibacterial modified siloxane and tetramethylammonium hydroxide siliconate were mixed in a mass ratio of 1:0.6:0.6:0.02, nitrogen was passed for 15 minutes, and the mixture was stirred at 85°C and 150 r / min for 2.5 hours. Tetramethyldisiloxane (0.3 times the mass of octamethylcyclotetrasiloxane) was added, the temperature was raised to 100°C and stirring was continued for 8 hours. The temperature was raised to 135°C at 15°C / min and stirring was continued for 45 minutes. The mixture was distilled at 0.2 MPa for 1.5 hours to obtain functionalized polysiloxane.

[0038] (4) 2-chloro-4,6-diamino-1,3,5-triazine, anhydrous aluminum chloride and chlorobenzene were mixed uniformly in a mass ratio of 1:0.35:11, stirred at 250 r / min for 25 min at 1.5°C, and then 0.7 times the mass of resorcinol of 2-chloro-4,6-diamino-1,3,5-triazine was added, the temperature was raised to 80°C, stirred for 5 h, cooled naturally to room temperature, extracted and washed with chloroform for 4 times, and dried at 65°C for 11 h to obtain a light-absorbing monomer;

[0039] (5) The light-absorbing monomer, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde, urea and deionized water were mixed in a mass ratio of 1:1.5:12:5:80, the pH value was adjusted to 8.5 with triethanolamine, and the mixture was stirred at 400 r / min for 60 min at 70°C to obtain a prepolymer solution; n-hexadecane, sodium dodecyl sulfate, Tween-80 and deionized water were mixed in a mass ratio of 1:0.04:0.01:5 and the mixture was heated at room temperature for 1 The mixture was stirred at 900 r / min for 10 min to obtain an emulsion; the prepolymer solution was cooled to 50°C, the rotation speed was adjusted to 1900 r / min, an emulsion twice the mass of the prepolymer solution was added, the pH was adjusted to 2.5 with 10% ammonium chloride solution and 10% citric acid within 2.5 h, the mixture was stirred for 4 h, the mixture was cooled to room temperature, filtered, the residue was washed with deionized water and anhydrous ethanol for 4 times, and dried at 70°C for 4 h to obtain modified phase change microcapsules;

[0040] (6) The silk fibroin solution and the functionalized polysiloxane were mixed in a mass ratio of 1:0.6, concentrated at 25°C and 15 Pa to a solute mass fraction of 55%, and polyethylene glycol (0.015 times the mass of the silk fibroin solution) was added, and ultrasonic dispersion was carried out at 35°C and 30 kHz for 17.5 min to prepare a shell fluid; the modified phase change microcapsules and anhydrous ethanol were mixed in a mass ratio of 1:25, and ultrasonic dispersion was carried out at 35°C and 30 kHz for 17.5 min to prepare a core fluid; the shell fluid and the core fluid were passed through a vacuum evaporator. The fibers were extruded through a coaxial nozzle, the inner diameter of the nozzle outer ring was 0.7 mm, the inner diameter of the nozzle inner ring was 0.3 mm, the extrusion speed was 3 μL / min, the receiving distance was 11 cm, the spinning temperature was 25°C, the relative humidity was 45%, and the fibers were soaked in a 0.7 mol / L calcium chloride aqueous solution at 25°C for 17.5 s, taken out and immersed in a 1.4 g / L sodium carbonate aqueous solution, allowed to stand at 60°C for 70 min, taken out, washed 4 times with deionized water and anhydrous ethanol, and vacuum dried at 35°C for 7 h to obtain silk fibers.

[0041] (7) The silk fibers were warped on a warping machine and then woven into plain fabrics using a fully automatic rapier loom with a warp density of 600 yarns / 10 cm and a weft density of 500 yarns / 10 cm. The fabrics were then finished using a trifluoropropylene chloroplatinic acid mixed solution. The fabrics were double dipped and double rolled with a rolling rate of 80%. The fabrics were allowed to stand at 75°C for 15 min, heated to 120°C and allowed to stand for 30 min. The fabrics were then washed with deionized water for 10 min and air-dried to obtain silk fabrics.

[0042] Embodiment 3:

[0043] A method for preparing a silk fabric comprises the following steps:

[0044] (1) The silk cocoon was peeled into a single layer and placed in a 0.7% sodium carbonate aqueous solution, boiled for 30 minutes, cooled to room temperature, washed with deionized water for 5 times, and naturally air-dried to obtain degummed silk; the degummed silk and 10 mol / L lithium bromide aqueous solution were mixed at a mass ratio of 1:10, stirred at 800 r / min at 45°C for 30 minutes, centrifuged to obtain the supernatant, and diluted with 1.7 times the amount of deionized water, placed in a cellulose dialysis bag, and dialyzed with deionized water for 80 hours, and concentrated under vacuum at 30°C to a solute mass fraction of 40% to obtain a silk fibroin solution;

[0045] (2) Vinylmethyldimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and anhydrous ethanol were stirred at a mass ratio of 1:0.9:0.06:17 at 30°C and 600 r / min for 10 h to obtain flame-retardant modified siloxane; 3-chloropropyldimethoxymethylsilane, 3-dimethylaminochloropropane hydrochloride, and anhydrous ethanol were stirred at a mass ratio of 1:0.9:17 at 90°C and 600 r / min for 14 h to obtain antibacterial modified siloxane;

[0046] (3) Octamethylcyclotetrasiloxane, flame retardant modified siloxane, antibacterial modified siloxane and tetramethylammonium hydroxide siliconate were mixed in a mass ratio of 1:0.7:0.7:0.03, nitrogen was passed for 20 min, and the mixture was stirred at 200 r / min at 90 ° C for 3 h. Tetramethyldisiloxane (0.4 times the mass of octamethylcyclotetrasiloxane) was added, the temperature was raised to 105 ° C and stirring was continued for 9 h. The temperature was raised to 140 ° C at 20 ° C / min and stirring was continued for 50 min. The mixture was distilled at 0.3 MPa for 2 h to obtain functionalized polysiloxane.

[0047] (4) 2-chloro-4,6-diamino-1,3,5-triazine, anhydrous aluminum chloride and chlorobenzene were mixed uniformly in a mass ratio of 1:0.4:12, stirred at 300 r / min at 3°C ​​for 30 min, and then 0.8 times the mass of resorcinol of 2-chloro-4,6-diamino-1,3,5-triazine was added, the temperature was raised to 85°C, stirred for 6 h, cooled naturally to room temperature, extracted and washed with chloroform for 5 times, and dried at 70°C for 12 h to obtain a light-absorbing monomer;

[0048] (5) The light-absorbing monomer, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde, urea and deionized water were mixed in a mass ratio of 1:1.6:14:6:90, the pH value was adjusted to 8.7 with triethanolamine, and the mixture was stirred at 450 r / min for 70 min at 75°C to prepare a prepolymer solution; n-hexadecane, sodium dodecyl sulfate, Tween-80 and deionized water were mixed in a mass ratio of 1:0.05:0.012:6 and the mixture was heated at room temperature for 20 00r / min and stirred for 15min to obtain an emulsion; the prepolymer solution was cooled to 55°C, the rotation speed was adjusted to 2000r / min, and an emulsion 2.2 times the mass of the prepolymer solution was added, and the pH was adjusted to 2.5 with 10% ammonium chloride solution and 10% citric acid within 2.5h, and the reaction was stirred for 5h, cooled to room temperature, and filtered, and the filter residue was washed with deionized water and anhydrous ethanol for 5 times respectively, and dried at 75°C for 5h to obtain modified phase change microcapsules;

[0049] (6) The silk fibroin solution and functionalized polysiloxane were mixed at a mass ratio of 1:0.7, concentrated at 30°C and 20Pa to a solute mass fraction of 60%, and polyethylene glycol (0.02 times the mass of the silk fibroin solution) was added, and ultrasonic dispersion was carried out at 40°C and 35kHz for 20 minutes to prepare a shell fluid; the modified phase change microcapsules and anhydrous ethanol were mixed at a mass ratio of 1:30, and ultrasonic dispersion was carried out at 40°C and 35kHz for 20 minutes to prepare a core fluid; the shell fluid and the core fluid were separated by a coaxial Nozzle extrusion spinning, the inner diameter of the nozzle outer ring is 0.7mm, the inner diameter of the nozzle inner ring is 0.3mm, the extrusion speed is 3.2μL / min, the receiving distance is 12cm, the spinning temperature is 27℃, the relative humidity is 50%, soaked in a 0.8mol / L calcium chloride aqueous solution at 30℃ for 20s, taken out and immersed in a 1.5g / L sodium carbonate aqueous solution, left to stand at 65℃ for 80min, taken out, washed with deionized water and anhydrous ethanol 5 times, and vacuum dried at 40℃ for 8h to obtain silk fibers;

[0050] (7) The silk fibers were warped on a warping machine and then woven into plain fabrics using a fully automatic rapier loom with a warp density of 600 strands / 10 cm and a weft density of 500 strands / 10 cm. The fabrics were then treated with a mixed solution of trifluoropropylene chloroplatinic acid as a post-finishing solution, followed by two immersions and two rollings with a rolling residue rate of 80%. The fabrics were allowed to stand at 70-80°C for 20 min, heated to 130°C and allowed to stand for 40 min, washed with deionized water for 12 min, and air-dried to obtain silk fabrics.

[0051] Comparative Example 1:

[0052] A method for preparing a silk fabric comprises the following steps:

[0053] (1) The silkworm cocoons were peeled into a single layer and placed in a 0.6% by mass sodium carbonate aqueous solution, boiled for 27.5 min, cooled to room temperature, washed with deionized water for 4 times, and naturally air-dried to obtain degummed silk; the degummed silk and 9.5 mol / L lithium bromide aqueous solution were mixed in a mass ratio of 1:9, stirred at 700 r / min at 40°C for 27.5 min, centrifuged to obtain the supernatant, diluted with 1.6 times the amount of deionized water, placed in a cellulose dialysis bag, and dialyzed with deionized water for 75 h, and concentrated under vacuum at 25°C to a solute mass fraction of 37.5% to obtain a silk fibroin solution;

[0054] (2) 3-chloropropyldimethoxymethylsilane, 3-dimethylaminochloropropane hydrochloride, and anhydrous ethanol were stirred at 80°C and 500 r / min for 12 h to prepare antibacterial modified siloxane;

[0055] (3) Octamethylcyclotetrasiloxane, antibacterial modified siloxane and tetramethylammonium hydroxide siliconate were mixed in a mass ratio of 1:0.6:0.02, nitrogen was passed for 15 minutes, and the mixture was stirred at 85°C and 150 r / min for 2.5 hours. Tetramethyldisiloxane (0.3 times the mass of octamethylcyclotetrasiloxane) was added, the temperature was raised to 100°C and stirring was continued for 8 hours. The temperature was raised to 135°C at 15°C / min and stirring was continued for 45 minutes. The mixture was distilled at 0.2 MPa for 1.5 hours to obtain functionalized polysiloxane.

[0056] (4) 2-chloro-4,6-diamino-1,3,5-triazine, anhydrous aluminum chloride and chlorobenzene were mixed uniformly in a mass ratio of 1:0.35:11, stirred at 250 r / min for 25 min at 1.5°C, and then 0.7 times the mass of resorcinol of 2-chloro-4,6-diamino-1,3,5-triazine was added, the temperature was raised to 80°C, stirred for 5 h, cooled naturally to room temperature, extracted and washed with chloroform for 4 times, and dried at 65°C for 11 h to obtain a light-absorbing monomer;

[0057] (5) The light-absorbing monomer, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde, urea and deionized water were mixed in a mass ratio of 1:1.5:12:5:80, the pH value was adjusted to 8.5 with triethanolamine, and the mixture was stirred at 400 r / min for 60 min at 70°C to obtain a prepolymer solution; n-hexadecane, sodium dodecyl sulfate, Tween-80 and deionized water were mixed in a mass ratio of 1:0.04:0.01:5 and the mixture was heated at room temperature for 1 The mixture was stirred at 900 r / min for 10 min to obtain an emulsion; the prepolymer solution was cooled to 50°C, the rotation speed was adjusted to 1900 r / min, an emulsion twice the mass of the prepolymer solution was added, the pH was adjusted to 2.5 with 10% ammonium chloride solution and 10% citric acid within 2.5 h, the mixture was stirred for 4 h, the mixture was cooled to room temperature, filtered, the residue was washed with deionized water and anhydrous ethanol for 4 times, and dried at 70°C for 4 h to obtain modified phase change microcapsules;

[0058] (6) The silk fibroin solution and the functionalized polysiloxane were mixed in a mass ratio of 1:0.6, concentrated at 25°C and 15 Pa to a solute mass fraction of 55%, and polyethylene glycol (0.015 times the mass of the silk fibroin solution) was added, and ultrasonic dispersion was carried out at 35°C and 30 kHz for 17.5 min to prepare a shell fluid; the modified phase change microcapsules and anhydrous ethanol were mixed in a mass ratio of 1:25, and ultrasonic dispersion was carried out at 35°C and 30 kHz for 17.5 min to prepare a core fluid; the shell fluid and the core fluid were passed through a vacuum evaporator. The fibers were extruded through a coaxial nozzle, the inner diameter of the nozzle outer ring was 0.7 mm, the inner diameter of the nozzle inner ring was 0.3 mm, the extrusion speed was 3 μL / min, the receiving distance was 11 cm, the spinning temperature was 25°C, the relative humidity was 45%, and the fibers were soaked in a 0.7 mol / L calcium chloride aqueous solution at 25°C for 17.5 s, taken out and immersed in a 1.4 g / L sodium carbonate aqueous solution, allowed to stand at 60°C for 70 min, taken out, washed 4 times with deionized water and anhydrous ethanol, and vacuum dried at 35°C for 7 h to obtain silk fibers.

[0059] (7) The silk fibers were warped on a warping machine and then woven into plain fabrics using a fully automatic rapier loom with a warp density of 600 yarns / 10 cm and a weft density of 500 yarns / 10 cm. The fabrics were then finished using a trifluoropropylene chloroplatinic acid mixed solution. The fabrics were double dipped and double rolled with a rolling rate of 80%. The fabrics were allowed to stand at 75°C for 15 min, heated to 120°C and allowed to stand for 30 min. The fabrics were then washed with deionized water for 10 min and air-dried to obtain silk fabrics.

[0060] Comparative Example 2:

[0061] A method for preparing a silk fabric comprises the following steps:

[0062] (1) The silkworm cocoons were peeled into a single layer and placed in a 0.6% by mass sodium carbonate aqueous solution, boiled for 27.5 min, cooled to room temperature, washed with deionized water for 4 times, and naturally air-dried to obtain degummed silk; the degummed silk and 9.5 mol / L lithium bromide aqueous solution were mixed in a mass ratio of 1:9, stirred at 700 r / min at 40°C for 27.5 min, centrifuged to obtain the supernatant, diluted with 1.6 times the amount of deionized water, placed in a cellulose dialysis bag, and dialyzed with deionized water for 75 h, and concentrated under vacuum at 25°C to a solute mass fraction of 37.5% to obtain a silk fibroin solution;

[0063] (2) Vinylmethyldimethoxysilane, p-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and anhydrous ethanol were stirred at 25°C and 500 r / min for 9 hours to prepare flame retardant modified siloxane;

[0064] (3) Octamethylcyclotetrasiloxane, flame retardant modified siloxane and tetramethylammonium hydroxide siliconate were mixed in a mass ratio of 1:0.6:0.02, nitrogen was passed for 15 minutes, and the mixture was stirred at 85°C and 150 r / min for 2.5 hours. Tetramethyldisiloxane (0.3 times the mass of octamethylcyclotetrasiloxane) was added, the temperature was raised to 100°C and stirring was continued for 8 hours. The temperature was raised to 135°C at 15°C / min and stirring was continued for 45 minutes. The mixture was distilled at 0.2 MPa for 1.5 hours to obtain functionalized polysiloxane.

[0065] (4) 2-chloro-4,6-diamino-1,3,5-triazine, anhydrous aluminum chloride and chlorobenzene were mixed uniformly in a mass ratio of 1:0.35:11, stirred at 250 r / min for 25 min at 1.5°C, and then 0.7 times the mass of resorcinol of 2-chloro-4,6-diamino-1,3,5-triazine was added, the temperature was raised to 80°C, stirred for 5 h, cooled naturally to room temperature, extracted and washed with chloroform for 4 times, and dried at 65°C for 11 h to obtain a light-absorbing monomer;

[0066] (5) The light-absorbing monomer, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde, urea and deionized water were mixed in a mass ratio of 1:1.5:12:5:80, the pH value was adjusted to 8.5 with triethanolamine, and the mixture was stirred at 400 r / min for 60 min at 70°C to obtain a prepolymer solution; n-hexadecane, sodium dodecyl sulfate, Tween-80 and deionized water were mixed in a mass ratio of 1:0.04:0.01:5 and the mixture was heated at room temperature for 1 The mixture was stirred at 900 r / min for 10 min to obtain an emulsion; the prepolymer solution was cooled to 50°C, the rotation speed was adjusted to 1900 r / min, an emulsion twice the mass of the prepolymer solution was added, the pH was adjusted to 2.5 with 10% ammonium chloride solution and 10% citric acid within 2.5 h, the mixture was stirred for 4 h, the mixture was cooled to room temperature, filtered, the residue was washed with deionized water and anhydrous ethanol for 4 times, and dried at 70°C for 4 h to obtain modified phase change microcapsules;

[0067] (6) The silk fibroin solution and the functionalized polysiloxane were mixed in a mass ratio of 1:0.6, concentrated at 25°C and 15 Pa to a solute mass fraction of 55%, and polyethylene glycol (0.015 times the mass of the silk fibroin solution) was added, and ultrasonic dispersion was carried out at 35°C and 30 kHz for 17.5 min to prepare a shell fluid; the modified phase change microcapsules and anhydrous ethanol were mixed in a mass ratio of 1:25, and ultrasonic dispersion was carried out at 35°C and 30 kHz for 17.5 min to prepare a core fluid; the shell fluid and the core fluid were passed through a vacuum evaporator. The fibers were extruded through a coaxial nozzle, the inner diameter of the nozzle outer ring was 0.7 mm, the inner diameter of the nozzle inner ring was 0.3 mm, the extrusion speed was 3 μL / min, the receiving distance was 11 cm, the spinning temperature was 25°C, the relative humidity was 45%, and the fibers were soaked in a 0.7 mol / L calcium chloride aqueous solution at 25°C for 17.5 s, taken out and immersed in a 1.4 g / L sodium carbonate aqueous solution, allowed to stand at 60°C for 70 min, taken out, washed 4 times with deionized water and anhydrous ethanol, and vacuum dried at 35°C for 7 h to obtain silk fibers.

[0068] (7) The silk fibers were warped on a warping machine and then woven into plain fabrics using a fully automatic rapier loom with a warp density of 600 yarns / 10 cm and a weft density of 500 yarns / 10 cm. The fabrics were then finished using a trifluoropropylene chloroplatinic acid mixed solution. The fabrics were double dipped and double rolled with a rolling rate of 80%. The fabrics were allowed to stand at 75°C for 15 min, heated to 120°C and allowed to stand for 30 min. The fabrics were then washed with deionized water for 10 min and air-dried to obtain silk fabrics.

[0069] Comparative Example 3:

[0070] A method for preparing a silk fabric comprises the following steps:

[0071] (1) The silkworm cocoons were peeled into a single layer and placed in a 0.6% by mass sodium carbonate aqueous solution, boiled for 27.5 min, cooled to room temperature, washed with deionized water for 4 times, and naturally air-dried to obtain degummed silk; the degummed silk and 9.5 mol / L lithium bromide aqueous solution were mixed in a mass ratio of 1:9, stirred at 700 r / min at 40°C for 27.5 min, centrifuged to obtain the supernatant, diluted with 1.6 times the amount of deionized water, placed in a cellulose dialysis bag, and dialyzed with deionized water for 75 h, and concentrated under vacuum at 25°C to a solute mass fraction of 37.5% to obtain a silk fibroin solution;

[0072] (2) 2-chloro-4,6-diamino-1,3,5-triazine, anhydrous aluminum chloride and chlorobenzene were mixed uniformly in a mass ratio of 1:0.35:11, stirred at 250 r / min for 25 min at 1.5°C, and then 0.7 times the mass of resorcinol of 2-chloro-4,6-diamino-1,3,5-triazine was added, the temperature was raised to 80°C, stirred for 5 h, cooled naturally to room temperature, extracted and washed with chloroform for 4 times, and dried at 65°C for 11 h to obtain a light-absorbing monomer;

[0073] (3) The light-absorbing monomer, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde, urea and deionized water were mixed in a mass ratio of 1:1.5:12:5:80, the pH value was adjusted to 8.5 with triethanolamine, and the mixture was stirred at 400 r / min for 60 min at 70°C to prepare a prepolymer solution; n-hexadecane, sodium dodecyl sulfate, Tween-80 and deionized water were mixed in a mass ratio of 1:0.04:0.01:5 and the mixture was heated at room temperature for 1 The mixture was stirred at 900 r / min for 10 min to obtain an emulsion; the prepolymer solution was cooled to 50°C, the rotation speed was adjusted to 1900 r / min, an emulsion twice the mass of the prepolymer solution was added, the pH was adjusted to 2.5 with 10% ammonium chloride solution and 10% citric acid within 2.5 h, the mixture was stirred for 4 h, the mixture was cooled to room temperature, filtered, the residue was washed with deionized water and anhydrous ethanol for 4 times, and dried at 70°C for 4 h to obtain modified phase change microcapsules;

[0074] (4) The silk fibroin solution was concentrated to a solute mass fraction of 55% at 25°C and 15Pa, and polyethylene glycol (0.015 times the mass of the silk fibroin solution) was added, and ultrasonic dispersion was carried out at 35°C and 30kHz for 17.5min to prepare a shell fluid; the modified phase change microcapsules and anhydrous ethanol were mixed at a mass ratio of 1:25, and ultrasonic dispersion was carried out at 35°C and 30kHz for 17.5min to prepare a core fluid; the shell fluid and the core fluid were extruded and spun through a coaxial nozzle, The inner diameter of the outer ring of the nozzle is 0.7 mm, the inner diameter of the inner ring of the nozzle is 0.3 mm, the extrusion speed is 3 μL / min, the receiving distance is 11 cm, the spinning temperature is 25°C, the relative humidity is 45%, and the fiber is soaked in a 0.7 mol / L calcium chloride aqueous solution at 25°C for 17.5 seconds, taken out and immersed in a 1.4 g / L sodium carbonate aqueous solution, and allowed to stand at 60°C for 70 minutes, taken out, washed with deionized water and anhydrous ethanol 4 times, and vacuum dried at 35°C for 7 hours to obtain silk fibers;

[0075] (5) The silk fibers were warped on a warping machine and then woven into plain fabrics using a fully automatic rapier loom with a warp density of 600 strands / 10 cm and a weft density of 500 strands / 10 cm. The fabrics were then finished using a trifluoropropylene chloroplatinic acid mixed solution. The fabrics were double dipped and double rolled with a rolling rate of 80%. The fabrics were allowed to stand at 75°C for 15 min, heated to 120°C and allowed to stand for 30 min. The fabrics were then washed with deionized water for 10 min and air-dried to obtain silk fabrics.

[0076] Comparative Example 4:

[0077] A method for preparing a silk fabric comprises the following steps:

[0078] (1) The silkworm cocoons were peeled into a single layer and placed in a 0.6% by mass sodium carbonate aqueous solution, boiled for 27.5 min, cooled to room temperature, washed with deionized water for 4 times, and naturally air-dried to obtain degummed silk; the degummed silk and 9.5 mol / L lithium bromide aqueous solution were mixed in a mass ratio of 1:9, stirred at 700 r / min at 40°C for 27.5 min, centrifuged to obtain the supernatant, diluted with 1.6 times the amount of deionized water, placed in a cellulose dialysis bag, and dialyzed with deionized water for 75 h, and concentrated under vacuum at 25°C to a solute mass fraction of 37.5% to obtain a silk fibroin solution;

[0079] (2) Vinylmethyldimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and anhydrous ethanol were stirred at 25°C and 500 r / min for 9 hours at a mass ratio of 1:0.8:0.05:15 to obtain flame-retardant modified siloxane; 3-chloropropyldimethoxymethylsilane, 3-dimethylaminochloropropane hydrochloride, and anhydrous ethanol were stirred at 80°C and 500 r / min for 12 hours at a mass ratio of 1:0.8:15 to obtain antibacterial modified siloxane;

[0080] (3) Octamethylcyclotetrasiloxane, flame retardant modified siloxane, antibacterial modified siloxane and tetramethylammonium hydroxide siliconate were mixed in a mass ratio of 1:0.6:0.6:0.02, nitrogen was passed for 15 minutes, and the mixture was stirred at 85°C and 150 r / min for 2.5 hours. Tetramethyldisiloxane (0.3 times the mass of octamethylcyclotetrasiloxane) was added, the temperature was raised to 100°C and stirring was continued for 8 hours. The temperature was raised to 135°C at 15°C / min and stirring was continued for 45 minutes. The mixture was distilled at 0.2 MPa for 1.5 hours to obtain functionalized polysiloxane.

[0081] (4) 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde, urea and deionized water were mixed in a mass ratio of 1.5:12:5:80, the pH value was adjusted to 8.5 with triethanolamine, and the mixture was stirred at 400 r / min for 60 min at 70°C to obtain a prepolymer solution; n-hexadecane, sodium dodecyl sulfate, Tween-80 and deionized water were mixed in a mass ratio of 1:0.04:0.01:5, and the mixture was stirred at room temperature for 1900 r / min. / min and stirred for 10min to obtain an emulsion; the prepolymer solution was cooled to 50°C, the rotation speed was adjusted to 1900r / min, an emulsion twice the mass of the prepolymer solution was added, the pH was adjusted to 2.5 with 10% ammonium chloride solution and 10% citric acid within 2.5h, the reaction was stirred for 4h, the mixture was cooled to room temperature, filtered, the filter residue was washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 70°C for 4h to obtain modified phase change microcapsules;

[0082] (5) The silk fibroin solution and the functionalized polysiloxane were mixed at a mass ratio of 1:0.6, concentrated at 25°C and 15 Pa to a solute mass fraction of 55%, and polyethylene glycol (0.015 times the mass of the silk fibroin solution) was added, and ultrasonic dispersion was carried out at 35°C and 30 kHz for 17.5 min to prepare a shell fluid; the modified phase change microcapsules and anhydrous ethanol were mixed at a mass ratio of 1:25, and ultrasonic dispersion was carried out at 35°C and 30 kHz for 17.5 min to prepare a core fluid; the shell fluid and the core fluid were passed through a vacuum evaporator. The fibers were extruded through a coaxial nozzle, the inner diameter of the nozzle outer ring was 0.7 mm, the inner diameter of the nozzle inner ring was 0.3 mm, the extrusion speed was 3 μL / min, the receiving distance was 11 cm, the spinning temperature was 25°C, the relative humidity was 45%, and the fibers were soaked in a 0.7 mol / L calcium chloride aqueous solution at 25°C for 17.5 s, taken out and immersed in a 1.4 g / L sodium carbonate aqueous solution, allowed to stand at 60°C for 70 min, taken out, washed 4 times with deionized water and anhydrous ethanol, and vacuum dried at 35°C for 7 h to obtain silk fibers.

[0083] (6) The silk fibers were warped on a warping machine and then woven into plain fabrics using a fully automatic rapier loom with a warp density of 600 yarns / 10 cm and a weft density of 500 yarns / 10 cm. The fabrics were then finished using a trifluoropropylene chloroplatinic acid mixed solution. The fabrics were double dipped and double rolled with a rolling rate of 80%. The fabrics were allowed to stand at 75°C for 15 min, heated to 120°C and allowed to stand for 30 min. The fabrics were then washed with deionized water for 10 min and air-dried to obtain silk fabrics.

[0084] Comparative Example 5:

[0085] A method for preparing a silk fabric comprises the following steps:

[0086] (1) The silkworm cocoons were peeled into a single layer and placed in a 0.6% by mass sodium carbonate aqueous solution, boiled for 27.5 min, cooled to room temperature, washed with deionized water for 4 times, and naturally air-dried to obtain degummed silk; the degummed silk and 9.5 mol / L lithium bromide aqueous solution were mixed in a mass ratio of 1:9, stirred at 700 r / min at 40°C for 27.5 min, centrifuged to obtain the supernatant, diluted with 1.6 times the amount of deionized water, placed in a cellulose dialysis bag, and dialyzed with deionized water for 75 h, and concentrated under vacuum at 25°C to a solute mass fraction of 37.5% to obtain a silk fibroin solution;

[0087] (2) Vinylmethyldimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and anhydrous ethanol were stirred at 25°C and 500 r / min for 9 hours at a mass ratio of 1:0.8:0.05:15 to obtain flame-retardant modified siloxane; 3-chloropropyldimethoxymethylsilane, 3-dimethylaminochloropropane hydrochloride, and anhydrous ethanol were stirred at 80°C and 500 r / min for 12 hours at a mass ratio of 1:0.8:15 to obtain antibacterial modified siloxane;

[0088] (3) Octamethylcyclotetrasiloxane, flame retardant modified siloxane, antibacterial modified siloxane and tetramethylammonium hydroxide siliconate were mixed in a mass ratio of 1:0.6:0.6:0.02, nitrogen was passed for 15 minutes, and the mixture was stirred at 85°C and 150 r / min for 2.5 hours. Tetramethyldisiloxane (0.3 times the mass of octamethylcyclotetrasiloxane) was added, the temperature was raised to 100°C and stirring was continued for 8 hours. The temperature was raised to 135°C at 15°C / min and stirring was continued for 45 minutes. The mixture was distilled at 0.2 MPa for 1.5 hours to obtain functionalized polysiloxane.

[0089] (4) The silk fibroin solution and the functionalized polysiloxane were mixed in a mass ratio of 1:0.6, concentrated to a solute mass fraction of 55% at 25°C and 15Pa, and polyethylene glycol (0.015 times the mass of the silk fibroin solution) was added, and ultrasonic dispersion was performed at 35°C and 30kHz for 17.5min to obtain a shell fluid; deionized water was used as the core fluid; the shell fluid and the core fluid were extruded and spun through a coaxial nozzle, the inner diameter of the outer ring of the nozzle was 0.7mm, the inner diameter of the inner ring of the nozzle was 0.3mm, the extrusion speed was 3μL / min, the receiving distance was 11cm, the spinning temperature was 25°C, the relative humidity was 45%, and the fibers were soaked in a 0.7mol / L calcium chloride aqueous solution at 25°C for 17.5s, taken out and immersed in a 1.4g / L sodium carbonate aqueous solution, allowed to stand at 60°C for 70min, taken out, washed 4 times with deionized water and anhydrous ethanol, and vacuum dried at 35°C for 7h to obtain silk fibers;

[0090] (5) The silk fibers were warped on a warping machine and then woven into plain fabrics using a fully automatic rapier loom with a warp density of 600 strands / 10 cm and a weft density of 500 strands / 10 cm. The fabrics were then finished using a trifluoropropylene chloroplatinic acid mixed solution. The fabrics were double dipped and double rolled with a rolling rate of 80%. The fabrics were allowed to stand at 75°C for 15 min, heated to 120°C and allowed to stand for 30 min. The fabrics were then washed with deionized water for 10 min and air-dried to obtain silk fabrics.

[0091] Test Example 1:

[0092] Impact resistance test: The fabrics of each embodiment and each comparative example were cut to prepare standard specimens according to GB / T 3923.1 standard, and the breaking strength was measured. The results are shown in Table 1.

[0093] Table 1

[0094]

[0095] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the silk fabric prepared by the present invention has good breaking strength.

[0096] By comparison, the breaking strength of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that the quaternary ammonium salt cations on the functionalized polysiloxane and the negatively charged silk fibroin solution are adsorbed on each other through the electrostatic effect, thereby improving the breaking strength of the silk fabric; the breaking strength of Examples 1 to 3 is significantly greater than that of Comparative Example 3, indicating that the abundant chlorine on the functionalized polysiloxane reacts with the amino groups on the silk fibroin to form a stable chemical crosslink, thereby improving the breaking strength of the silk fabric; the breaking strength of Examples 1 to 3 is greater than that of Comparative Example 5, indicating that 2-vinyl-4,6-diamino-1,3,5-triazine participates in the preparation of modified phase change microcapsules, introduces double bonds on the surface of the phase change microcapsules, and reacts with the silicon hydrogen at both ends of the functionalized polysiloxane to form a stable crosslink, thereby improving the breaking strength of the silk fabric.

[0097] Test Example 2:

[0098] Flame retardant performance test method: According to GB / T 5454-2008 "Textile Combustion Performance Test Oxygen Index Method", each embodiment and each ratio are made into a standard sample with a size of 130mm×13mm×3mm, and the limiting oxygen index is tested using an FTT oxygen index tester; test temperature: 10℃~30℃; relative humidity: 30%~80%;. The results are shown in Table 2.

[0099] Table 2

[0100]

[0101] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the silk fabric prepared by the present invention has good flame retardant properties.

[0102] By comparison, the limiting oxygen index of Examples 1 to 3 is significantly greater than that of Comparative Example 2, indicating that the flame-retardant modified siloxane is prepared by reacting vinylmethyldimethoxysilane with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and the flame retardant DOPO is introduced into the silk fabric. The phosphorus-containing flame retardant can rapidly dehydrate and carbonize the fabric to form a dense protective carbon layer, isolate oxygen and reduce the thermal decomposition rate, thereby improving the flame retardant properties of the silk fabric; the limiting oxygen index of Examples 1 to 3 is significantly greater than that of Comparative Example 3, indicating that the abundant silicon on the polysiloxane can form a silicon-phosphorus synergistic flame retardant with the phosphorus element, thereby effectively improving the flame retardant properties of the silk fabric; the limiting oxygen index of Examples 1 to 3 is significantly greater than that of Comparative Example 5, indicating that the triazine structure introduced in the preparation process of the phase change microcapsule contains abundant nitrogen elements, which can block the diffusion of combustible gases and heat during the combustion process, and form nitrogen-silicon-phosphorus synergistic flame retardant with the silicon-phosphorus on the functionalized polysiloxane, thereby further improving the flame retardant properties of the silk fabric.

[0103] Test Example 3:

[0104] Anti-ultraviolet performance test: According to the standard specified in GB / T 18830, the anti-ultraviolet performance of the real fabric was tested using a textile ultraviolet protection factor tester (model: Labsphere UV-1000F). The results are shown in Table 3.

[0105] Table 3

[0106]

[0107] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the silk fabric prepared by the present invention has good anti-ultraviolet performance.

[0108] By comparison, the UPF values ​​of Examples 1 to 3 are greater than those of Comparative Examples 4 and 5, indicating that the m-diphenol and triazine structures react to form a conjugated hydrogen bonded six-membered ring, which absorbs ultraviolet light through the stretching vibration of hydrogen bonds, thereby improving the anti-ultraviolet performance of the silk fabric.

[0109] Test Example 4:

[0110] Antibacterial performance test: The materials of each embodiment and comparative example were crushed into powders of less than 150 microns, and the same mass was taken to test the antibacterial rate of the materials against Staphylococcus aureus according to the Quine test method. The results are shown in Table 4.

[0111] Table 4

[0112]

[0113] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 4, it can be found that the silk fabric prepared by the present invention has good antibacterial properties.

[0114] By comparison, the antibacterial rates of Examples 1 to 3 are significantly greater than that of Comparative Example 2, indicating that 3-chloropropyldimethoxymethylsilane and 3-dimethylaminochloropropane hydrochloride react to generate quaternary ammonium salt to prepare antibacterial modified siloxane. Quaternary ammonium salt as a cationic antibacterial agent has good contact antibacterial effect, thereby improving the antibacterial properties of silk fabrics.

[0115] Test Example 5:

[0116] Warmth retention performance test: According to the flat plate heat dissipation instrument method in GB / T 11048-2008 "Determination of thermal resistance and moisture resistance of textiles under steady-state conditions for physiological comfort", each embodiment and each comparative example was prepared into a 30 cm × 30 cm sample, and the test temperature was set to 20 ± 0.1 ° C, the relative humidity was 60 ± 5%, and the test plate temperature was set to 35 ° C to test the thermal resistance. The results are shown in Table 5.

[0117] Table 5

[0118]

[0119] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 5, it can be found that the silk fabric prepared by the present invention has good warmth retention performance.

[0120] By comparison, the thermal resistance of Examples 1 to 3 is significantly greater than that of Comparative Example 4, indicating that the meta-diphenol and triazine structures react to form a conjugated hydrogen-bonded six-membered ring, which absorbs ultraviolet light through the stretching vibration of hydrogen bonds, and converts light energy into heat energy, thereby improving the thermal insulation performance of the silk fabric; the thermal resistance of Examples 1 to 3 is significantly greater than that of Comparative Example 5, indicating that the modified phase change microcapsules prepared by encapsulating n-hexadecane with light-absorbing monomers, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde, and urea, and the conjugated hydrogen-bonded six-membered ring formed by the reaction of meta-diphenol and triazine structures can convert light energy into heat energy for storage and slow release through phase change microcapsules, thereby improving the thermal insulation effect of the silk fabric.

[0121] Test Example 6

[0122] Hydrophobic performance test: The water contact angle of silk fabric was tested using a German Krüss DSA 100 contact angle tester. The volume of the water droplet in the water contact angle measurement was 6 μL. The results are shown in Table 6.

[0123] Table 6

[0124]

[0125] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 5, it can be found that the silk fabric prepared by the present invention has good hydrophobic properties.

[0126] By comparison, the contact angles of Examples 1 to 3 are significantly greater than the contact angle of Comparative Example 3, indicating that the silicon-hydrogen bonds at both ends of the functionalized polysiloxane form stable chemical crosslinks with the double bonds on the finishing agent trifluoropropylene, thereby improving the hydrophobic properties of the silk fabric.

[0127] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a silk fabric, characterized in that: The method comprises the following preparation steps: (1) degumming silkworm cocoons to prepare a silk fibroin solution; (2) Vinylmethyldimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and anhydrous ethanol were stirred at 400-600 r / min for 8-10 h at 20-30° C. to obtain flame retardant modified siloxane; 3-chloropropyldimethoxymethylsilane, 3-dimethylaminochloropropane hydrochloride, and anhydrous ethanol were stirred at 400-600 r / min for 10-14 h at 70-90° C. to obtain antibacterial modified siloxane; Methylcyclotetrasiloxane, flame retardant modified siloxane, antibacterial modified siloxane and tetramethylammonium hydroxide silicon alkoxide are mixed in a mass ratio of 1: (0.5-0.7): (0.5-0.7): (0.01-0.03), nitrogen is passed for 10-20 minutes, and the mixture is stirred at 100-200 r / min for 2-3 hours at 80-90° C., tetramethyldisiloxane with a mass of 0.2-0.4 times of octamethylcyclotetrasiloxane is added, the mixture is heated to 95-105° C. and stirred for 7-9 hours, the mixture is heated to 130-140° C. at a rate of 10-20° C. / min and stirred for 40-50 minutes, and the mixture is distilled at 0.1-0.3 MPa for 1-2 hours to obtain functionalized polysiloxane; (3) mixing 2-chloro-4,6-diamino-1,3,5-triazine, anhydrous aluminum chloride, chlorobenzene and resorcinol to obtain a light absorbing monomer; (4) n-hexadecane, sodium dodecyl sulfate, Tween-80 and deionized water in a mass ratio of 1: (0.03-0.05): (0.008-0.012): (4-6) were mixed, and stirred at 1800-2000 r / min for 5-15 min at room temperature to obtain an emulsion; the light-absorbing monomer, 2-vinyl-4,6-diamino-1,3,5-triazine, formaldehyde, urea and deionized water were mixed in a mass ratio of 1: (1.4-1.6): (10-14): (4-6): (70-90), and the pH value was adjusted to 8.3-8.7 with triethanolamine, and heated at 65-75°C for 350-450 r / min stirring for 50-70 minutes to obtain a prepolymer solution; cooling the prepolymer solution to 45-55°C, adjusting the rotation speed to 1800-2000r / min, adding an emulsion 1.8-2.2 times the mass of the prepolymer solution, adjusting the pH to 2.5 with 10% ammonium chloride solution and 10% citric acid within 2.5 hours, stirring for 3-5 hours, cooling to room temperature, filtering, washing the filter residue with deionized water and anhydrous ethanol for 3-5 times respectively, and drying at 65-75°C for 3-5 hours to obtain modified phase change microcapsules; (5) The modified phase change microcapsules and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(20-30), and ultrasonically dispersed at 30-40°C and 25-35kHz for 15-20min to obtain a core fluid; the silk fibroin solution and the functionalized polysiloxane are uniformly mixed in a mass ratio of 1:(0.5-0.7), and concentrated at 20-30°C and 10-20Pa to a solute mass fraction of 50%-60%, and polyethylene glycol (0.01-0.02 times the mass of the silk fibroin solution) is added, and ultrasonically dispersed at 30-40°C and 25-35kHz for 15-20min to obtain a shell fluid; the shell fluid and the core fluid are separated by the same method; Axial nozzle extrusion spinning, the inner diameter of the nozzle outer ring is 0.7mm, the inner diameter of the nozzle inner ring is 0.3mm, the extrusion speed is 2.8-3.2μL / min, the receiving distance is 10-12cm, the spinning temperature is 23-27℃, the relative humidity is 40%-50%, soaking in a 0.6-0.8mol / L calcium chloride aqueous solution at 20-30℃ for 15-20s, taking out and immersing in a 1.3-1.5g / L sodium carbonate aqueous solution, standing at 55-65℃ for 60-80min, taking out, washing with deionized water and anhydrous ethanol for 3-5 times, and vacuum drying at 30-40℃ for 6-8h to obtain silk fiber; (6) The silk fibers are spun into fabrics, and then finished with a trifluoropropylene-chloroplatinic acid mixed solution to obtain silk fabrics.

2. The method for preparing a silk fabric according to claim 1, characterized in that: The specific preparation steps of the silk fibroin solution in step (1) are as follows: peeling the silk cocoon into a single layer and placing it in a sodium carbonate aqueous solution with a mass fraction of 0.5% to 0.7%, boiling it for 25 to 30 minutes, cooling it to room temperature, washing it with deionized water for 3 to 5 times, and naturally air-drying it to obtain degummed silk; mixing the degummed silk and a 9 to 10 mol / L lithium bromide aqueous solution at a mass ratio of 1: (8 to 10), stirring it at 600 to 800 r / min at 35 to 45° C. for 25 to 30 minutes, centrifuging and separating the supernatant, diluting it with deionized water 1.5 to 1.7 times the supernatant, placing it in a cellulose dialysis bag, dialyzing it with deionized water for 70 to 80 hours, and concentrating it under vacuum at 20 to 30° C. to a solute mass fraction of 35% to 40%; The silkworm cocoon is a double palace cocoon.

3. The method for preparing a silk fabric according to claim 1, characterized in that: The reaction process of the functionalized polysiloxane in step (2) is as follows:

4. The method for preparing a silk fabric according to claim 1, characterized in that: The specific preparation steps of the light-absorbing monomer in step (3) are as follows: 2-chloro-4,6-diamino-1,3,5-triazine, anhydrous aluminum chloride and chlorobenzene are mixed uniformly in a mass ratio of 1:(0.3-0.4):(10-12), stirred at 200-300 r / min for 20-30 min at 0-3° C., and then 0.6-0.8 times the mass of resorcinol of 2-chloro-4,6-diamino-1,3,5-triazine is added, the temperature is raised to 75-85° C., stirred for 4-6 h, cooled naturally to room temperature, extracted and washed with chloroform for 3-5 times, and dried at 60-70° C. for 10-12 h.

5. The method for preparing a silk fabric according to claim 1, characterized in that: The specific preparation steps of the silk fabric in step (6) are as follows: the silk fibers are warped by a warping machine and then woven into a plain fabric by a fully automatic rapier loom, with a warp density of 600 strands / 10 cm and a weft density of 500 strands / 10 cm, to obtain the fabric, using a trifluoropropylene chloroplatinic acid mixed solution as a post-finishing liquid, double dipping and double rolling, with a rolling rate of 80%, standing at 70-80° C. for 10-20 min, heating to 110-130° C. and standing for 20-40 min, washing with deionized water for 8-12 min and then drying; The trifluoropropylene chloroplatinic acid mixed solution is prepared by mixing trifluoropropylene, chloroplatinic acid and dichloromethane in a mass ratio of 1:0.1:3.

Citation Information

Patent Citations

  • Antistatic fabric and preparation method thereof

    CN116497474A

  • Moisture-absorbing antibacterial fabric and preparation method thereof

    CN118390190A